2004
DOI: 10.1242/dev.01366
|View full text |Cite
|
Sign up to set email alerts
|

Dynactin is required to maintain nuclear position within postmitoticDrosophilaphotoreceptor neurons

Abstract: How a nucleus is positioned within a highly polarized postmitotic animal cell is not well understood. In this work, we demonstrate that the Dynactin complex (a regulator of the microtubule motor protein Dynein) is required to maintain the position of the nucleus within post-mitotic Drosophila melanogaster photoreceptor neurons. We show that multiple independent disruptions of Dynactin function cause a relocation of the photoreceptor nucleus toward the brain, and that inhibiting Dynactin causes the photorecepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 57 publications
4
60
0
Order By: Relevance
“…CPs are thought to stabilize the barbed end of the Arp1 microfilament in the Dynactin complex, which is required for transport along microtubules (Schafer et al, 1994). cpa and cpb, like other Dynactin complex subunits, are required to maintain the position of nuclei in Drosophila photoreceptor neurons (Whited et al, 2004) (and data not shown). However, removal of kinesin heavy chain (khc), which counteracts Dynein/Dynactin-based transport, failed to rescue extrusion of cpa mutant cells in the wing disc (see Fig.…”
Section: Actin Capping Proteins Maintain Epithelial Integritymentioning
confidence: 97%
“…CPs are thought to stabilize the barbed end of the Arp1 microfilament in the Dynactin complex, which is required for transport along microtubules (Schafer et al, 1994). cpa and cpb, like other Dynactin complex subunits, are required to maintain the position of nuclei in Drosophila photoreceptor neurons (Whited et al, 2004) (and data not shown). However, removal of kinesin heavy chain (khc), which counteracts Dynein/Dynactin-based transport, failed to rescue extrusion of cpa mutant cells in the wing disc (see Fig.…”
Section: Actin Capping Proteins Maintain Epithelial Integritymentioning
confidence: 97%
“…Moreover, in photoreceptor cells the nuclei fail to move apically toward the minus-end of microtubules, and instead remain at more basal locations. Informatively, this nuclear positioning phenotype can be suppressed by mutations in subunits of Kinesin, the plus-end directed microtubule motor (Whited et al, 2004). Finally, in green alga, post-mitotic nuclear migration is mediated in part by a Kinesin-1 protein (Holzinger and Lutz-Meindl, 2002).…”
Section: Proteins For Movingmentioning
confidence: 99%
“…Other antibodies were obtained from DSHB (University of Iowa, IA, USA). Immunoblotting and immunohistochemistry were as described previously (Sears et al, 2003;Whited et al, 2004).…”
Section: Histology and Immunoblottingmentioning
confidence: 99%